Gene expression of peripheral blood mononuclear cells and CD8+ T cells from gilts after PRRSV infection - Lagumdzic, Emil; Pernold, Clara P. S.; Ertl, Reinhard; Palmieri, Nicola; Stadler, Maria; Sawyer, Spencer; Stas, Melissa R.; Kreutzmann, Heinrich; Rümenapf, Till; Ladinig, Andrea; Saalmüller, Armin (Frontiers in Immunology, 2023)
Porcine reproductive and respiratory syndrome virus (PRRSV) is a positive-stranded RNA virus, which emerged in Europe and U.S.A. in the late 1980s and has since caused huge economic loses. Infection with PRRSV causes mild to severe respiratory and reproductive clinical symptoms in pigs. Alteration of the host immune response by PRRSV is associated with the increased susceptibility to secondary viral and bacterial infections resulting in more serious and chronic disease. However, the expression profiles underlying innate and adaptive immune responses to PRRSV infection are yet to be further elucidated. In this study, we investigated gene expression profiles of PBMCs and CD8+ T cells after PRRSV AUT15-33 infection. We identified the highest number of differentially expressed genes in PBMCs and CD8+ T cells at 7 dpi and 21 dpi, respectively. The gene expression profile of PBMCs from infected animals was dominated by a strong innate immune response at 7 dpi which persisted through 14 dpi and 21 dpi and was accompanied by involvement of adaptive immunity. The gene expression pattern of CD8+ T cells showed a strong adaptive immune response to PRRSV, leading to the formation of highly differentiated CD8+ T cells starting from 14 dpi. The hallmark of the CD8+ T-cell response was the increased expression of effector and cytolytic genes (PRF1, GZMA, GZMB, GZMK, KLRK1, KLRD1, FASL, NKG7), with the highest levels observed at 21 dpi. Temporal clustering analysis of DEGs of PBMCs and CD8+ T cells from PRRSV-infected animals revealed three and four clusters, respectively, suggesting tight transcriptional regulation of both the innate and the adaptive immune response to PRRSV. The main cluster of PBMCs was related to the innate immune response to PRRSV, while the main clusters of CD8+ T cells represented the initial transformation and differentiation of these cells in response to the PRRSV infection. Together, we provided extensive transcriptomics data explaining gene signatures of the immune response of PBMCs and CD8+ T cells after PRRSV infection. Additionally, our study provides potential biomarker targets useful for vaccine and therapeutics development.